2012
DOI: 10.1097/ana.0b013e3182611a30
|View full text |Cite
|
Sign up to set email alerts
|

Indication for Surgery and the Risk of Postoperative Nausea and Vomiting After Craniotomy

Abstract: MVD and AN resection were associated with an increased likelihood of PONV compared with craniotomies performed for other tumor resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In neurosurgical patients, a 40-80% incidence of PONV within 24 h after craniotomy was reported [18,19]. Moreover, several observational studies demonstrated that infratentorial surgeries were associated with a higher incidence of PONV [2,20,21]. For instance, Meng concluded that PONV frequently occurs in adults recovering from retromastoid craniectomy with microvascular decompression of cranial nerves [22].…”
Section: Discussionmentioning
confidence: 99%
“…In neurosurgical patients, a 40-80% incidence of PONV within 24 h after craniotomy was reported [18,19]. Moreover, several observational studies demonstrated that infratentorial surgeries were associated with a higher incidence of PONV [2,20,21]. For instance, Meng concluded that PONV frequently occurs in adults recovering from retromastoid craniectomy with microvascular decompression of cranial nerves [22].…”
Section: Discussionmentioning
confidence: 99%
“…In neurosurgical patients, a 40-80% incidence of PONV within 24 h after craniotomy was reported [18,19]. Moreover, several observational studies demonstrated that infratentorial surgeries were associated with a higher incidence of PONV [2,20,21]. For instance, Meng concluded that PONV frequently occurs in adults recovering from retromastoid craniectomy with microvascular decompression of cranial nerves [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several observational studies demonstrated that infratentorial surgeries were associated with a higher incidence of PONV [2,20,21]. For instance, Meng concluded that PONV frequently occurs in adults recovering from retromastoid craniectomy with microvascular decompression of cranial nerves [22].…”
Section: Discussionmentioning
confidence: 99%
“…It receives input from the chemoreceptor trigger zone, vestibular apparatus, cerebellum, and solitary tract [24]. Inadvertent or unavoidable interference with these areas may cause release of humoral factors that may be stimuli for PONV [2]. Conceivably, infratentorial craniotomy was an especially high-risk factor for PONV in patients undergoing craniotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation